Diagnostic and clinical application value of magnetic resonance imaging (MRI) for progressive massive fibrosis of coal worker pneumoconiosis: Case reports. Issue 20 (May 2017) - Zhang, Lansheng; Wang, Chun; Yan, Qiuyue; Zhang, Tao; Han, Zhengxiang; Jiang, Guan
Abstract: Rationale: Using magnetic resonance imaging (MRI), we diagnosed pneumoconiosis by identifying the content and distribution of hydrogen protons in the water molecules in different tissues and lesions. Patient concerns: 25 cases of CWP patients with progressive massive fibrosis (PMF) lesions. Diagnoses: Patients were correctly diagnosed, with one case each of Phase I and II pneumoconiosis and 23 cases of Phase III pneumoconiosis. Interventions: None. Outcomes: Through MRI, 39 PMF pneumoconiosis lesions exhibited equal, low or equally low, and uneven signals on T2WI and fat suppression (SPIR) (38/39, 37/39). Lessons: MRI has good specificity to identify the characteristics of PMF lesions of CWP, as well as has high application value for the differential diagnosis of lung cancer and other lung tumor-like lesions.